First visceral leishmaniasis focus in Argentina - Salomón, Oscar Daniel (2008)
An eight-year old boy from Posadas (27º 23’ S, 55º 54’ W) was diagnosed with visceral leishmaniasis (VL) dur-ing 2006. Lutzomyia longipalpiswas discovered in the backyard of his house, while the spread of canine visceral leishmaniasis was confirmed in Posadas. This is the southernmost report of a VL transmission focus and the first in Argentina.